The Role of the Gerbang Hebat Program in Minimizing the Decline in Polite Language Use in Elementary Schools - Retno Wulandari; Wahdan Najib Habiby (FKIP - Universitas Riau, 2026)
This study examines the contribution of the Gerbang Hebat Program in reducing the decline of language etiquette among fourth-grade students at SDN 2 Kadipaten, Boyolali. Using a quantitative ex post facto correlational design, the research involved 38 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through correlation coefficients, coefficient of determination, simple linear regression, F-test, and t-test. Descriptive findings indicate that students’ language politeness was generally in the good category, with an average score of 57.97 across seven indicators: consideration, respect, humility, courtesy, tactfulness, respectfulness, and appropriate word choice. Hypothesis testing revealed that the Gerbang Hebat Program significantly contributed to students’ language politeness (t = 2.097 > 2.028; sig. = 0.043), supported by the regression equation Y = 35.978 + 0.629X. However, the coefficient of determination (R² = 0.109) shows that the program accounts for only 10.9% of the variation, while 89.1% is influenced by other factors. These findings suggest that although the Gerbang Hebat Program provides a positive foundation for developing language etiquette, its effectiveness should be strengthened through greater collaboration between schools and families, alongside better supervision of digital media exposure.